Persistence of DNMT3A R882 mutations during remission does not adversely affect outcomes of patients with acute myeloid leukaemia. (1st August 2016) - Bhatnagar, Bhavana; Eisfeld, Ann‐Kathrin; Nicolet, Deedra; Mrózek, Krzysztof; Blachly, James S.; Orwick, Shelley; Lucas, David M.; Kohlschmidt, Jessica; Blum, William; Kolitz, Jonathan E.; Stone, Richard M.; Bloomfield, Clara D.; et al.
Summary: Somatic mutation of the DNMT3A gene at the arginine R882 site is common in acute myeloid leukaemia (AML). The prognostic significance of DNMT3A R882 mutation clearance, using traditional diagnostic next generation sequencing (NGS) methods, during complete remission (CR) in AML patients is controversial. We examined the impact of clearing DNMT3A R882 mutations at diagnosis to the detectable threshold of ˂3% during CR on outcome in 56 adult AML patients. Mutational remission, defined as clearance of pre‐treatment DNMT3A R882 and all other AML‐associated mutations to a variant allele frequency ˂3%, occurred in 14 patients whereas persistent DNMT3A R882 mutations were observed in 42 patients. There were no significant differences in disease‐free or overall survival between patients with and without DNMT3A R882 mutation clearance. Patients with persistent DNMT3A R882 who cleared all other AML mutations and did not acquire new mutations ( n  = 30), trended towards longer disease‐free survival (1·6 vs. 0·6 years, P  =   0·06) than patients with persistence of DNMT3A R882, in addition to other mutations or acquisition of new AML‐associated mutations, such as those in TET2, JAK2, ASXL1 and TP53 ( n  = 12). These data demonstrate that DNMT3A R882 mutations, as assessed by traditional NGS methods, persist in the majority of AML patients in CR.